Analysis of the motor behaviour of people without specific dance training in improvisation tasks: Influence of mirror and partner - Pérez-Calzado, E.; Coterón, J.; Ric, Á.; Torrents, C. (Journal of Sports Sciences, 2025)
This study aims to analyse the influence of the mirror and/or partner constraints on the motor creativity of women without specific training in dance during improvisation tasks, in order to contribute to the knowledge of creativity in the field of sports science and movement-based practices. We studied the exploratory behaviour and emerging movement patterns of 12 women who performed four improvisations under the following situations: individual without mirror; individual with mirror; partner without mirror; and partner with mirror. The dynamic overlap qd(t) was calculated to identify the exploratory dynamics composed of the exploratory amplitude and the rate of change between movement configurations. To determine emerging movement patterns, a principal component analysis was carried out by ad hoc routines prepared. A mixed linear model was performed to find out the influence of the different constraints on the exploratory behaviour. The results indicate that the presence of the mirror seems to provoke a decrease in the exploratory behaviour. In addition, partner improvisation favoured coupling and imitation dynamics among the participants. Likewise, the most recurrent emergent movement pattern was walking while moving the arms. It would be advisable to take the influence of these constraints into consideration depending on the improvisation purpose and the experience level of female participants.